Sex-Related Memory Recall and Talkativeness for Emotional Stimuli - Arnone, Benedetto; Pompili, Assunta; Tavares, Clotilde; Gasbarri, Antonella (Frontiers in Behavioral Neuroscience, 2011)
Recent studies have evidenced an increasing interest in sex-related brain mechanisms and cerebral lateralization subserving emotional memory, language processing, and conversational behavior. We used event related potentials (ERP) to examine the influence of sex and hemisphere on brain responses to emotional stimuli. Given that the P300 component of ERP is considered a cognitive neuroelectric phenomenon, we compared left and right hemisphere P300 responses to emotional stimuli in men and women. As indexed by both amplitude and latency measures, emotional stimuli elicited more robust P300 effects in the left hemisphere in women than in men, while a stronger P300 component was elicited in the right hemisphere in men compared to women. Our findings show that the variables of sex and hemisphere interacted significantly to influence the strength of the P300 component to the emotional stimuli. Emotional stimuli were also best recalled when given a long-term, incidental memory test, a fact potentially related to the differential P300 waves at encoding. Moreover, taking into account the sex-related differences in language processing and conversational behaviour, in the present study we evaluated possible talkativeness differences between the two genders in the recollection of emotional stimuli. Our data showed that women used a higher number of words, compared to men, to describe both arousal and neutral stories. Moreover, the present results support the view that sex differences in lateralization may not be a general feature of language processing but may be related to the specific condition, such as the emotional content of stimuli.